Psychological skills training programme : anxiety control for soccer players (penalty kicks) - Fatin Aqillah Mohamed Ridzwan (2018)
The aim of the proposed study is to examine the effectiveness of psychological skills training (PST) programme, which includes goal setting, attention concentration and confidence building, in controlling anxiety when taking penalty kicks under anxiety-induced situations. Participants were 20 universities- or club-level soccer players (males = 10, females = 10), with at least 5 years of playing experience, who completed 4 psychological questionnaires (ACSI, CSAI-2, SCAT and TSCI) to assess participants’ confidence level, state and trait anxiety level and their coping skills. Correlation tests were carried out to determine if there was a relationship between the scores of the same subscales and penalty kicks, pre and post-PST. A two-way repeated measures ANOVA was used to determine if there was a difference between the scores of the questionnaires and penalty kicks pre and post-PST. There were significant, positive and negative correlations between some subscales of the questionnaires but there was a significant, positive relationship between the subscales pre and post-PST. There were significant differences in ACSI, CSAI-2, TSCI and penalty kicks scores pre and post-PST but no significant difference in SCAT scores, which measures trait anxiety. This is probably due to trait anxiety being a personality characteristic rather than a momentary feeling. In conclusion, the PST programme can be beneficial in controlling anxiety when taking penalty kicks.